Vietnam Students' National Defence and Security Education: Challenges and Solutions - CAO, Ngoc Bau; TRAN, Mong Nghi (Journal of Ecohumanism, 2024)
This study looks at how national defense and security education (NDSE) is now taught to Vietnamese students, emphasizing how important it is for promoting patriotism and a sense of national identity. Utilizing current policy advancements and real-world experiences, we examine major issues and suggest tactical fixes to raise the caliber and efficacy of this training program. Our results highlight the necessity of updating curricula, improving preparation for teachers, and fortifying institutional support in order to fulfill the changing requirements of national security within the framework of global integration.Using a mixed-methods approach, the study combines quantitative data from Vietnamese educational institutions with stakeholder interviews and policy analysis. We examine the NDSE's historical background in Vietnam, how it changed over time in response to shifting geopolitical conditions, and how it is currently used at different educational levels. The study also looks at how relevant and successful NDSE is in educating Vietnam's youth for their futures as informed and involved citizens, according to students, educators, and policymakers.Although NDSE has come a long way in recent years, our analysis shows that maintaining student interest, assuring uniform quality of instruction across institutions, and integrating the curriculum with current security threats remain formidable obstacles. We provide a thorough framework for improving NDSE, along with suggestions for innovative pedagogy, curriculum revision, and better resource management. In addition, we talk about how NDSE may become more relevant and interesting to the younger generation by incorporating technology and practical learning techniques.Beyond Vietnam, the research's implications provide guidance to other countries facing the difficulty of teaching their youth about national security issues in a globe growing more interconnected by the day. This research adds to the larger conversation on civic education and national identity creation in the light of globalization and rapid technological change by critically analyzing Vietnam's approach to NDSE.